YURAK-QON TOMIR TIZIMINING FIZIOLOGIYASI VA ARTERIAL GIPERTENZIYA MEXANIZMLARI (Multidisciplinary Journal of Science and Technology, 2025)
This article explores the fundamental physiological mechanisms of the cardiovascular system and the pathogenesis of arterial hypertension. The interplay between the heart and blood vessels, the role of neurohumoral regulation of blood pressure, and the underlying pathophysiological factors contributing to hypertension are thoroughly examined. In addition, modern diagnostic techniques and effective treatment strategies are discussed. The study provides theoretical and practical insights into the prevention and management of cardiovascular diseases.